Pattern of Elevated Serum Alkaline Phosphatase (ALP) Levels in Hospitalized Patients: A Single Centre Study (Pulse, 2014)
Background: Persistent elevation of serum ALP is frequently encountered and can pose a diagnostic dilemma due to its association with a wide range of clinical conditions. However, the significance of ALP in these clinical conditions in routine practice is often underestimated or overrated. Objectives: This study was determined to assess the pattern of ALP with an aim to elucidate its clinical utility among hospitalized patients. Method & materials: The inpatients with high ALP level were enlisted & analysed between January to December 2012 excluding cases of (a) patients who have bone involvements with malignancies and (b) HIV-seropositive patients attending a tertiary care Hospital at Dhaka. Extremely high levels of ALP were defined as being more than 1000 U/L. These patients were divided into different groups according to their final diagnosis. Results: A total of 154 hospitalized patients with eligible medical records were identified (98 male and 56 female, mean age 36 years). Their ALP levels are ranging from 1,006 to 3,067 IU/L; very extreme values of > 3000 IU/L being rarely (only about 2%) documented. Patients with sepsis can have an extremely high alkaline phosphatase level (1,648.2 ± 328.4 IU/L) and a normal bilirubin. Conclusion: High serum ALP levels in hospitalized patients were commonly found in three major groups having obstructive biliary diseases, infiltrative liver disease and sepsis. A variety of other causes were also noted. This routine laboratory test should receive more attention in clinical decision-making than has previously been given. DOI: http://dx.doi.org/10.3329/pulse.v6i1-2.20329 Pulse Vol.6 January-December 2013 p.20-26